Desenvolvimento de hidrotalcitas de Ni-Mg-Al como recursores na formação de oxidos mistos e suas aplicações em processos catalíticos de reforma de metano com CO2 - Carantón, Alberth Renne González (2011)
In this work were prepared hydrotalcites (LDHs - Layered Double Hydroxides) Ni-Mg-Al to be used as precursors in the preparation of mixed oxides Ni-Mg-Al. The effect of incorporation of the particles, the calcination temperature and nickel content were the variables chosen in order to observe the influence of factors such as degree of dispersion, textural properties, crystal structure and catalytic activity in the reaction reforming of methane with CO2. LDHs stable of Ni-Mg-Al were prepared by sol-gel method. The incorporation of nickel particles was done by drip consecutive solutions of nickel acetate tetrahydrate in ethanol after the network formation of Mg-Al by intercalation and ion exchange of the LDHs of Mg-Al with solution of complex of Ni+2(EDTA )-2. The calcination was studied by keeping a constant heating rate (5°C/min) And making changes in the temperature levels of 500 and 650°C, respectively. Were chosen for three levels of nickel with respect to the percentage of total mass in LHDs. After the incorporation of nickel particles, gels were dried and calcined to form the mixed oxide Ni-Mg-Al, in case of direct incorporation in alcoholic medium, the gel obtained was aged for 18 hours, dried at 70 ° C for 24 hours, calcined for 5 hours and stored. In the case of LDHs obtained by ion exchange, the Mg-Al gel was aged for 18 hours to complete the hydrolysis by addition of stoichiometric amounts of water. Finally, the gel was dried at 80 ° C, resulting in the Mg-Al LDHs. The incorporation of nickel occurred adding the hydrotalcite to complex solution of Ni+2(EDTA)-2 with high agitation and at room temperature for 24 hours, allowing the ion exchange. The gel was centrifuged at 150 rpm, washed and dried 70 ° C for 24 hours and calcined for 16 hours. The samples were characterized by x-ray diffraction (EDX), physisorption BET with nitrogen, X-ray diffraction (XRD), temperature programmed reduction (TPR), desorption of hydrogen temperatureprogrammed (TPD), temperature programmed oxidation (TPO) and transmission electron microscopy (TEM). The catalysts were applied to methane reforming with CO2. The distribution of products and parameters such as conversion, yield and H2/CO ratio were made measuring in catalyst stability iv tests kinetic parameters with respect to time. Some catalysts were tested in extreme conditions of deposition of coke in order to investigate the deposition and the effect of variables in your control. Met the requirements for proper preparation and activation of these oxides as a function of stability observed in the catalytic reforming reaction of methane with CO2 and control the deposition of coke. The characterization results, together with the results of catalytic tests support the idea that the catalytic activity, stability and control in the deposition strongly depend on the steps of incorporation of nickel particles on the network, which are influenced by the particle content, degree of sintering and type of interactions between the structure Mg-Al and Ní+2.